Perancangan Aplikasi Monitoring Kalori Sebagai Upaya Pencegahan Penyakit Diabetes Mellitus Berbasis Android - Diyah Intan Pramitha Sari; Restyandito Restyandito; Kristian Adi Nugraha (Maranatha University Press, 2022)
There are still many people who pay less attention to calories, both the amount of calorie needs of the body and the number of calories that have been consumed. One of the contributing factors is the difficulty of manually calculating the number of calories itself. Meanwhile, consulting with nutritionists is expensive.It's very risky for health. So made an application monitoring the number of calories. It applies goal directed design (GDD) method. In this study, usability test was conducted using 3 aspects of usability, namely effectiveness, efficiency, and satisfaction in accordance with ISO-9241-11 standard that produces effectiveness value of 97%, efficiency value of 66%, and satisfaction value of 86.75%. A total of 92.5% of respondents felt helped in calculating their calorie count. 97.5% of respondents felt more alert to diabetes after using the app, and 62.5% of respondents said that they would re-use the app for daily use in the future.